Implementación de un sistema de control de temperatura para un fermentador de cerveza artesanal. - Lanchimba Ruiz, Darwin Fabricio (2021)
It is intended to generate an improvement initiative in a homemade fermentation process and take it to an industrial level, which tries to develop a prototype capable of effectively controlling the temperature in a hermetically sealed environment to help in the beer fermentation process. to the people who do it in an artisanal way in small quantities, therefore the cost of an automated fermenter that is exactly used in this type of fermentation processes and meets the requirements to improve the quality of the product that in turn buy is analyzed. an industrial one is extremely expensive. Temperature control in the craft beer fermentation process is essential in the area of product quality, which is why it is identified that temperature control in the environment where artisans ferment the product is not adequate. Therefore, to design a hermetic chamber with temperature control for the craft beer fermentation process by means of a PID control with which the quality of the beer will be improved with a constant control during a period established by the owner. Also, the concepts related to the theory of temperature control will be described, the characteristics of the microcontroller used for the control system and the design process of the fermenter with its cooling and heating system inside the hermetic chamber suitable for the process are mentioned. Therefore, making a prototype of an efficient automated fermenter with a lower cost than the commercial one known at the industrial level, since it can be demonstrated that quality products can also be generated within the country and compete at the world level. al.